أدوات التحلیل النوعى فى العلوم الانسانیة والاجتماعیة :دراسة تحلیلیة مقارنة - د. احمد ماهر خفاجة (المجلة الدولية لعلوم المكتبات والمعلومات)
Purpose- The purpose of this paper is to report the findings of a study to explorequalitative data analysis software used among social sciences and humanitiesresearchers. Also, the study tried to reveal the possibility of using these tools byArab social sciences and humanities scholars.Additionally, the study tried to find the best software that can handle data in theArabic language and how these tools function with Arabic documents. Moreover,the study explored other functions provided by these tools that may pose a greatbenefit for Arab researchers.Design/methodology/approach- The study adopted a comparative analyticalapproach to explore the characteristics of the qualitative analysis tools and theirrelevance to the Arab user, also their compatibility with the Arabic texts. Thestudy proposed a list of the most important technical and functional criteria thatrepresent the basis of any qualitative analysis software.Findings- The analysis of the interviews revealed that there are three qualitativeanalysis software that fit the Arab user’ needs and support the Arabic language,but the study has concluded that most of these programs showed some issuesand limitations while handling the Arabic data. The study recommended usingATLAS. ti software as it showed less problems while using it with the Arabic data.